EFFECT OF URANIUM NITRICUM IN LM POTENCIES ON REDUCTION IN CARDIOVASCULAR RISK AMONG PATIENT WITH TYPE 2 DIABETES MELLITUS - Ansari, Anwar Amir; Dole, Sanjeev M; Patil, Anita; Jadhav, Arun (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The present study was carried to determine the reduction in cardiovascular (CV) risk among the patients with type 2 diabetes mellitus (T2DM) after treatment with homeopathic uranium nitricum in LM potencies on the top of unstable background antidiabetic and lipid-modifying therapy. Methods: This study was open-label, placebo-controlled, parallel arm phase 3 study, stratified according to glycated hemoglobin values (<7.0, >7.0). Male and female patients with T2DM (>18 years old) were included in this study from Bharati Vidyapeeth Homeopathic Hospital, Pune. The CV risk was assessed through the United Kingdom Prospective Diabetes Study (UKPDS) search engine. This study was conducted during October 2014– December 2015. Results: Female prevalence was more (52.94%) than male (47.05%) in the current study. The average body mass index of the population was 26.98 (24.9, 29.1). The significant CV risk reduction (p<0.05) after treatment with uranium nitricum in LM potencies was observed for non-fatal and fatal coronary heart disease p< among the patients with patients with T2DM. Conclusion: The homeopathic formulation of uranium nitricum in LM potencies significantly reduces the CV risk when assessed through UKPDS search engine in the patients with T2DM on the background of unstable antidiabetic therapy and LMT.